2019
DOI: 10.1016/j.jid.2018.06.191
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Expression of A20/TNFAIP3 Controls Skin Inflammation Associated with Atopic Dermatitis and Psoriasis

Abstract: Keratinocytes are key players in chronic inflammatory skin diseases. A20 regulates NF-κB-dependent expression of proinflammatory genes and cell death, but the impact of its expression in keratinocytes on systemic inflammation and skin disorders has not been determined. Comparative transcriptomic analysis of microdissected epidermis showed that A20 is down-regulated in involved epidermis, but not in dermis, of psoriasis and atopic dermatitis patients, suggesting that loss of A20 expression in keratinocytes incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 71 publications
6
42
0
Order By: Relevance
“…Of note, cytokine expression decreased after treatment with TNF-α antagonists. Similarly, other studies reported that the severity of skin inflammation in epidermis-specific TNFAIP3-knockout mice was exacerbated and associated with the upregulation of proinflammatory cytokines and chemokines [7]. Another study showed that TNFAIP3 deficiency by siRNA silencing or in knockout cells led to enhanced IL-17-dependent inflammatory gene expression, which indicates that TNFAIP3 might be an inhibitor of IL-17 signaling [9].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Of note, cytokine expression decreased after treatment with TNF-α antagonists. Similarly, other studies reported that the severity of skin inflammation in epidermis-specific TNFAIP3-knockout mice was exacerbated and associated with the upregulation of proinflammatory cytokines and chemokines [7]. Another study showed that TNFAIP3 deficiency by siRNA silencing or in knockout cells led to enhanced IL-17-dependent inflammatory gene expression, which indicates that TNFAIP3 might be an inhibitor of IL-17 signaling [9].…”
Section: Discussionmentioning
confidence: 85%
“…The tumor necrosis factor alpha-induced protein 3 (TNFAIP3) gene encodes the TNFAIP3 protein, also known as TNF-α-inducible zinc finger protein A20, a cytoplasmic zinc-finger protein that acts as a negative immunoregulatory protein under inflammatory states [6]. A previous study showed that the selective deletion of TNFAIP3 in mice led to systemic inflammation under homeostatic conditions and the exacerbation of inflammatory skin disorders [7]. Of note, the TNFAIP3 mRNA expression levels in peripheral blood mononuclear cells (PBMCs) from patients with psoriasis were negatively correlated with disease severity in psoriasis vulgaris [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the current antipsoriatic therapies target T cell activation, there is increasing evidence for a critical role of keratinocytes. For instance, it was observed that the keratinocyte-specific loss of Tnfaip3, encoding the NF-κB inhibitor A20, is sufficient to induce psoriasis-like skin inflammation in mice (41). Likewise, keratinocyte overexpression of constitutively active Stat3, which we have previously identified as a transcriptional regulator of IκBζ (8), triggers spontaneous psoriatic lesions (42).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 53 human tissues characterized in the Genotype-Tissue Expression Project (Lonsdale et al, 2013), the skin has the highest LOC100130476 expression, suggesting its functional role in the skin. Moreover, the genomic locus of LOC100130476 is interesting; it is transcribed in antisense direction and overlaps partially with the gene body and promoter of TNFAIP3, which is a critical brake on NF-kB signaling and its absence in keratinocytes is sufficient to exacerbate inflammatory skin disorders by increasing cytokine and chemokine expression (Devos et al, 2019). Based on these facts, we decided to examine the expression and function of LOC100130476 in human skin wounds.…”
Section: Introductionmentioning
confidence: 99%